PENGUATAN MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) - Baharuddin, Baharuddin (Idaarah: Jurnal Manajemen Pendidikan, 2017)
School management with a strategic plan is considered successful if it is able to raise the quality of processes and products of quality education and learning. Therefore the ability of school principals, school personnel and others to implement a strategy within a school is very important, in relation to the ability of the principal as a leader and teachers as professionals responsible for the progress of learners. The principal is required to have the ability to manage and formulate the development of school vision, mission and objectives and to identify school programs that can support the learning process including curriculum, human resources, facilities and infrastructure, provision of guidance for educators, and dynamic active participation of parents, including institutions / institutions that have concern for education.